2019
DOI: 10.33963/kp.14966
|View full text |Cite
|
Sign up to set email alerts
|

Causes of death and morbidity in patients with atrial fibrillation after left atrial appendage occlusion

Abstract: Background Left atrial appendage occlusion (LAAO) is a safe and effective alternative for stroke prevention in patients with atrial fibrillation (AF). However, there is little literature on the exact causes of death and adverse events during follow-up after LAAO. aims The primary aim of this study was to evaluate survival free of any serious adverse events and of any-cause death in midterm follow-up. The secondary aims were to analyze causes of mortality and further hospitalization as well as adverse events, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Secondly, patients in Endocardial Group were significantly older and with multimorbidity, as evidenced of 18.2% cases of noncardiovascular mortality, with malignancy being leading cause of death. Causes of death and morbidity following Endocardial LAAC were discussed in detail in our previous report 34 . Therefore, we would like to strongly emphasize, that based on the current results, it cannot be concluded that mortality after endocardial approach is higher.…”
Section: Discussionmentioning
confidence: 62%
“…Secondly, patients in Endocardial Group were significantly older and with multimorbidity, as evidenced of 18.2% cases of noncardiovascular mortality, with malignancy being leading cause of death. Causes of death and morbidity following Endocardial LAAC were discussed in detail in our previous report 34 . Therefore, we would like to strongly emphasize, that based on the current results, it cannot be concluded that mortality after endocardial approach is higher.…”
Section: Discussionmentioning
confidence: 62%
“…Out of the 29 included studies, 27 reported the number of deaths in their studies. The incidence rates of all-cause death ranged from zero [ 22 , 25 , 28 , 32 ] to 11.4 events per 100 patient-years [ 18 ] (Fig. 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the last decades, the LAAO procedure emerged as an alternative method for stroke prevention 17 . Multiple observational studies point to the feasibility and safety of percutaneous endocardial and epicardial LAAO procedures, and present long‐term effectiveness in thromboembolism and bleeding risk reduction, even in high‐risk patients 16,18‐20 . Recently, the class of recommendations of percutaneous LAAO procedure was upgraded, and currently, both European and American guidelines recommend percutaneous LAAO procedure as an alternative treatment for patients with a high risk of stroke and contraindications for long‐term OAC use (Class IIb, Level of Evidence B) 6,7,21 .…”
Section: Discussionmentioning
confidence: 99%